ANALISIS TEKUK PADA DAERAH PLASTIS MENGGUNAKAN METODE GERARD DAN EKSPERIMEN - Triono, Agus (ROTASI, 2007)
Advanced studied of buckling phenomena in plastic region (crippling) is very important because the equations of this phenomena are semi-empirical equations only. The equations are collected from statistical studied from several experiment. One of those equations is founded by Gerard and used to be called Gerard Method. In this research, to proved this equation, crippling experiment of st ringer Al-7075 T6 and Al -7150 T7751 have been done at ITB Aerospace Engineering’s Structural Laboratory. From that experiment could be concluded that the equation of crippling could be used to analyzing crippling phenomena because the different between th eoritic and experi ment is about 1.73% to 12.24%